2017
DOI: 10.4103/jets.jets_131_16
|View full text |Cite
|
Sign up to set email alerts
|

Studying morbidity and predicting mortality in patients with blunt chest trauma using a novel clinical score

Abstract: Background:A departmental audit in March 2015 revealed significant mortality rate of 40% in blunt chest trauma patients (much greater than the global 25%). A study was thus planned to study morbidity and predictors of mortality in blunt chest trauma patients admitted to our hospital.Methods:This study was a prospective observational study of 139 patients with a history of blunt chest trauma between June 2015 and November 2015 after the Institutional Ethics Committee approval in April 2015. The sample size was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
6
0
3
Order By: Relevance
“…A review of literature has conveyed that morbidity and mortality rates increase relative to the location, number, and the presence of bilateral rib fractures, this being compounded by the development of haemothorax/pneumothorax or secondary pulmonary sequalae. The outcome of a clinical audit conducted by Manay et al concluded that the mortality rate in patients with missed chest injuries was 15.1% compared with 7.6% of patients who had their injuries diagnosed in the acute setting …”
Section: Discussionmentioning
confidence: 99%
“…A review of literature has conveyed that morbidity and mortality rates increase relative to the location, number, and the presence of bilateral rib fractures, this being compounded by the development of haemothorax/pneumothorax or secondary pulmonary sequalae. The outcome of a clinical audit conducted by Manay et al concluded that the mortality rate in patients with missed chest injuries was 15.1% compared with 7.6% of patients who had their injuries diagnosed in the acute setting …”
Section: Discussionmentioning
confidence: 99%
“…Manay et al, after evaluating patients with BCT, found that when the number of RF was !4 there was a statistically significant increase in mortality. 30 They also found that presence of head injury and GCS 8 was associated with an increase in mortality in BCT patients. In our study, the mortality in both the ET and LT groups was mainly due to TBI; however, all these subjects also had !5 fractured ribs.…”
Section: Variablementioning
confidence: 94%
“…However, the best analgesic technique in thoracic trauma is unclear. Manay et al [37] reported that Thoracic Epidural Analgesia (TEA) halved the number of days that the patients were intubated and significantly decreased the incidence of pneumonia. In a multicenter cohort study, Gage et al [38] concluded that TEA reduced mortality in patients with three or more rib fractures.…”
Section: The Paradigm Of Pain In Thoracic Traumamentioning
confidence: 99%